(untitled) (Revista de Ciências Agroveterinárias, 2006)
Cissus sicyoides (Vitaceae) is a widely distributed vine throughout the American Continent. Also known by the common English name of toad vine, one important use for this species is in the treatment of diabetes. Although preliminary investigations were unable to confirm this activity, recent studies have shown interesting hypoglicaemic action in the extracts. For this reason, the species has also become known by the common name of vegetable insulin. However, further clinical studies will have to be done in the future in order to justify the efficacy ans safety of C. sicyoides in the treatment of this ailment.